Sarcopenia and polypharmacy: A cross-sectional study among community-dwelling older adults in Saudi Arabia - Alharkan, Khalid; BuSaad, Mohammed A.; Alshami, Ali M; Shanb, Alsayed A.; Alnasser, Abdullah Hussain; Alsaihati, Mohammed Ibrahim; Alwail, Ali Tahir; AlYousef, Noor Hussain; Zainab Hassan AlSinan; Al-Sadah, Zahra Mohammed; AlNasser, Kawthar Ali; Fatemah Malik Aldawood; et al. (Acta Biomedica Atenei Parmensis, 2025)
Background and Aim: Sarcopenia, characterized by the progressive loss of muscle mass, strength, and function, is prevalent among older adults, often exacerbated by polypharmacy, defined as the concurrent use of five or more medications. This study aimed to investigate the prevalence of sarcopenia and its association with polypharmacy in community-dwelling older adults in Saudi Arabia. Methods: A cross-sectional study was conducted with a required sample size of 245, based on a 65% prevalence rate of sarcopenia among older adults in Saudi Arabia. A total of 267 participants, attending outpatient clinics at Imam Abdulrahman bin Faisal University and King Fahad Hospital, were assessed for sarcopenia using a Jamar hydraulic handheld dynamometer to measure handgrip strength. Results: The prevalence of sarcopenia was found to be 31.8%, significantly higher among individuals taking five or more medications (47.9%) compared to those on fewer medications (22.3%) (p < 0.001). There was no significant association between sarcopenia and falls in the previous 12 months. Patients with sarcopenia had a higher median age (69 years) than those without (64 years). Additionally, the mean body mass index (BMI) was lower in the sarcopenic group (25.9 kg/m²) compared to non-sarcopenic individuals (27.6 kg/m²) (p = 0.04). A higher prevalence of sarcopenia was noted in females (46.4%) versus males (26.2%). Conclusion: This study highlights a strong association between polypharmacy and increased risk of sarcopenia among older adults in Saudi Arabia, emphasizing the need for careful medication management in this population.